DECOLONISING LABOUR LAWS AND REPOSSESSING SUBALTERN EPISTEMOLOGIES: A REVIEW OF SOUTH AFRICAN AND NAMIBIAN MINEWORKERS’ FIGHT FOR LABOUR RIGHTS - Warikandwa, Tapiwa (Obiter, 2024)
In the historical and current transformation discourses in South Africa and Namibia, the concept of decolonisation is no longer a mere abstract concept. Decolonisation is now a fundamental policy and regulatory imperative that is heavily centred on, among other things, the land question and debates around the historical as well as present-day use of indigenous cheap and unskilled labour in underpaid sectors of industry –particularly the mining sector. During the colonial era, as the mining industries in South Africa and Namibia expanded, a substantial number of migrant labourers and local workers entered the mines. To safeguard these mineworkers’ legal rights, labour laws were passed. Despite the implementation of such labour laws, regular strikes were a feature of the mining industries in South Africa and Namibia at the time. In the post-colonial dispensation, the South African mining industry has been characterised by numerous strike actions, while in Namibia, widespread dissatisfaction with working conditions has been noted. This raises the question of whether or not South Africa and Namibia have made progress in defending mineworkers’ labour rights. This question is critical when viewed through the lens of a post-colonial society governed by a constitutionalised labour law framework. While there has arguably been a noticeable improvement in mineworkers’ employment conditions, labour-related inequities continue to characterise the mining industries in South Africa and Namibia in the post-colonial era. Profiteering, capitalism, safeguarding the security of tenure of foreign mining corporations, and the persistent need to ensure the ease of doing business in the mining sector appear to take precedence over defending mineworkers’ rights. Thus, this article explores the labour rights discourse developed by South African and Namibian mineworkers, as well as the applicable labour legislation. A strong case is made for reconsidering the extent to which South African and Namibian labour laws have been decolonised. This is done in a manner that is attentive to investment security and sustainable growth of the mining sector in the two countries as well as the realisation of African mineworkers’ fundamental labour rights.